Impact of Training Program on Self-Efficacy: An Empirical Study on the Faculty Members of Universities in Bangladesh - Islam, Ariful; Ali, Mohammad; Hasan, Noman (World Journal of Vocational Education and Training, 2020)
This study assesses the training effect on increasing self-efficacy of teachers in the tertiary level. It focuses on the necessity of teachers' training at the very beginning of their careers and the continuation of it at regular intervals. Though many pieces of research have been conducted on training, the actual gap lies in the quality measures of research especially for the development of a positive mindset. The data were collected by a non-probability sampling technique while the corresponding hypothesis was tested with linear regression. The findings indicate that there lies significant positive relationship between teachers' training and self-efficacy. The study will assist the policymakers and concerned authorities to initiate training sessions at the designed timeframe. Thus, the value of the training program should be used to gain a competitive advantage and it should be viewed as a medium to enhance the capacity of an individual as human capital.